2019
DOI: 10.17221/346/2019-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sowing density on grain yield, protein and oil content and plant morphology of soybean (Glycine max L. Merrill)

Abstract: To find out exactly how sowing density and sowing pattern affect soybean grain yield, quality and its components in non-traditional soybean growing regions, such as Germany, two field trials have been conducted at two locations in Bavaria in 2016 and 2017. The experiments were carried out with four sowing densities (30, 50, 70, 90 seeds/m<sup>2</sup>) and four cultivars from different maturity groups (Viola 000, Lissabon 000, ES Mentor 00, Orion 00) as randomized complete block design with four rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
25
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 21 publications
9
25
2
2
Order By: Relevance
“…The higher number of side branches and, consequently, more pods per plant, with precision seeding compared to drill seeding did not lead to an increase in protein or oil content in soybean. However, an increase in crop density tends to lead to higher protein content [51,52] and since the two, i.e., protein and oil content, correlate negatively [53], oil content also increases with decreasing crop density by trend [54]. Our results showed that neither drill nor precision seeding reduced or increased protein content and oil content.…”
Section: Discussionmentioning
confidence: 50%
“…The higher number of side branches and, consequently, more pods per plant, with precision seeding compared to drill seeding did not lead to an increase in protein or oil content in soybean. However, an increase in crop density tends to lead to higher protein content [51,52] and since the two, i.e., protein and oil content, correlate negatively [53], oil content also increases with decreasing crop density by trend [54]. Our results showed that neither drill nor precision seeding reduced or increased protein content and oil content.…”
Section: Discussionmentioning
confidence: 50%
“…An almost 100% correlation between a decrease in the yield of seeds and protein in soybean in the subsequent years indicates a significant effect of humidity on the value of both traits, however most probably without an essential change in the seed protein content. Popović et al (2012) claim that environment is a dominant element determining protein content in soybean seeds, regardless of the planting density (Sobko et al 2019).…”
Section: Resultsmentioning
confidence: 99%
“…These differences accounted for 5.40% and 6.60% less plants prior to harvest than after emergence, respectively. According to Sobko et al (2019), the planting density prior to harvest is usually lower than after full plants emergence. Similarly, Schmitz et al (2020) found the average 6.6% plant loss in the stand during growth, irrespective of the row spacing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to this result, Habtamu et al (2018) reported that the main effect of plant population did not show significant variations on harvest index of soybean cultivar. And, Sobko et al (2019) reported that the main effect of inter row spacing on harvest index was stable characteristic within a cultivar and was not affected by planting density of soybean cultivar.…”
Section: Hundred Grains Weightmentioning
confidence: 98%